BER ANALYSIS FOR OFDM USING WINDOWING AND EQUALIZATION TECHNIQUES - Bhardwaj, Nikhil (My University, 2014)
Wireless communications is emerging as the largest sectors of the telecommunications industry. Wireless communications system design is a very comprehensive field of study for the future. Its major challenges include increased spectral efficiency and improved link reliability. The radio channel which constitutes the propagation medium suffers from fading and interference from other users. A frequency selective fast time varying fading channel only can model such a hostile environment. It had established with studies that the multicarrier data transmission techniques such as the Orthogonal Frequency Division Multiplexing (OFDM) is best suited for such channels. The demand for high speed data services have been increasing, which is impossible to achieve by the conventional serial data transmission system without a trade-off between the data services and without the bandwidth of the system getting increased. OFDM can also be defined as a combination of modulation and multiplexing. In OFDM, ultimately the spectrum has to be shared with different sub-carriers. The multiplexing, in OFDM is applied to independent signals but they are the subset of the one main signal. Multipath generates two types of interferences at the receiver. Frequency selective fading and Inter symbol interference (ISI). The attraction of OFDM is mainly due to how the system handles these effects. The flatness perceived by a narrow band channel overcomes frequency selective fading and modulating at a very low symbol rate, makes the symbols much longer than the channel impulse response, and diminishes the ISI. Insertion of an extra guard interval between consecutive OFDM symbols reduces the ISI even more. While, using powerful error correcting codes and time or frequency interleaving yields even more robustness against frequency selective fading. The SNR vs. BER performance of the OFDM improves significantly using windowing and equalization techniques. Windowing technique had used for reducing the spectral side-lobes of OFDM. A popular window usually used for this purpose is the Raised-Cosine Window, due to its tapered and smooth edges. When the window function is applied to an OFDM signal, the spectrum reduces at the edges. Some reduction effect also takes place at the middle of the band as well. Whereas the equalization nullified the effect of channel during transmission of OFDM signal. Equalization can be performed by several equalizers composed by a single-tap at each frequency of the received signal. In this thesis, by adding Raised Cosine (RC) Window along with Equalization function in OFDM system with 16-QAM modulation technique, at 〖10〗^(-2.9) Bit Error Rate (BER) an improvement of 5 dB had achieved in the SNR value for AWGN Channel as compared to traditional OFDM system had achieved. An improvement of 15dB had achieved in the SNR value for Rayleigh Channel and an improvement of 24 dB had achieved in the SNR value for Rician Channel in the proposed OFDM system as compared to traditional OFDM system at 〖10〗^(-2.9) BER.
ME, ECED
Keywords: OFDM; Windowing; Equalization